Management of Super-Refractory Status Epilepticus with Isoflurane and Hypothermia - Zhumadilov, Agzam; Gilman, Charles P.; Viderman, Dmitriy (Frontiers in Neurology, 2015)
Super-refractory status epilepticus is status epilepticus that continues beyond 24 hours and includes those cases in which epilepsy is recurrent upon reduction or withdrawal of treatment. We describe the presentation and successful management of a male patient with super-refractory status epilepticus using the inhaled anesthetic, isoflurane, and mild hypothermia (HT). The potential utility of combined HT and volatile anesthesia is discussed.